Ion‐Free and Ion‐Pairing Assemblies of Anion‐Responsive π‐Electronic Systems Possessing Directly Linked Alkyl Chains. Issue 14 (30th June 2016) - Haketa, Yohei; Katayama, Daisuke; Fukunaga, Shinya; Bando, Yuya; Sakurai, Tsuneaki; Matsuda, Wakana; Seki, Shu; Maeda, Hiromitsu
Abstract: Alkyl‐substituted pyrrole‐based anion‐responsive π‐electronic systems formed supramolecular gels and liquid crystals through effective π–π stacking and van der Waals interactions. The addition of chloride as a planar cation salt afforded ion‐pairing assemblies as soft materials comprising planar receptor‐Cl − complexes and the cation. Abstract : Always responsive : Alkyl‐substituted pyrrole‐based anion‐responsive π‐electronic systems formed supramolecular gels and liquid crystals through effective π–π stacking and van der Waals interactions. The addition of chloride as a planar cation salt afforded ion‐pairing assemblies as soft materials comprising planar receptor‐Cl − complexes and the cation.